2007
DOI: 10.1111/j.1464-0597.2007.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruiters’ Perceptions and Use of Applicant Résumé Information: Screening the Recent Graduate

Abstract: Despite résumés being evaluated as an initial step in most employment decisions for professional-level job openings, researchers have not adequately examined the influence that applicants' résumé qualifications may have on recruiters' initial impressions of applicants' employability. Based on prior research, we hypothesised that recruiters' perceptions of job applicant employability will be associated with varying levels of job applicants' academic qualifications, work experience, and extracurricular activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
212
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(233 citation statements)
references
References 50 publications
15
212
5
1
Order By: Relevance
“…While resumes and applications provide much factual and verifiable information such as educational achievements, certifications, licenses, experience, and so on, employers also use them to infer other characteristics such as personality, intelligence, leadership, and work ethic (Cable & Gilovich, 1998;Cole, Feild, Giles, & Harris, 2009). They then use these inferences to assess prospect employability (Brown & Campion, 1994;Cole, Feild, & Giles, 2003;Cole, Rubin, Feild, & Giles, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While resumes and applications provide much factual and verifiable information such as educational achievements, certifications, licenses, experience, and so on, employers also use them to infer other characteristics such as personality, intelligence, leadership, and work ethic (Cable & Gilovich, 1998;Cole, Feild, Giles, & Harris, 2009). They then use these inferences to assess prospect employability (Brown & Campion, 1994;Cole, Feild, & Giles, 2003;Cole, Rubin, Feild, & Giles, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recently Cole, Rubin, Feild, and Giles' (2007) sample of 244 experienced recruiters evaluating actual resumes of recent or soon-to-be college graduates demonstrated that strong academic qualifications can account for weaker work experience and extracurricular activities but also that strong work experience and extracurricular activities can account for weaker academic qualifications. Nevertheless, having a strong background in academic performance, work experience, and extracurricular activities is likely to lead to high ratings regarding employment suitability (Cole et al, 2007).…”
Section: Educationmentioning
confidence: 99%
“…Nevertheless, having a strong background in academic performance, work experience, and extracurricular activities is likely to lead to high ratings regarding employment suitability (Cole et al, 2007). Overall, future research should address whether it is most effective to include GPA within major, overall GPA, or both within major and overall GPA.…”
Section: Educationmentioning
confidence: 99%
“…Various studies found that the students will get an extra learning experience by attending various extracurricular activities. Leadership skills, interpersonal skills, awareness, and self-confidence can be enhanced by engaging in extracurricular activities (Cole et al, 2007;Cole et al, 2003).…”
Section: The Involvement In Extracurricular Activitiesmentioning
confidence: 99%
“…Students' participation in extracurricular activities has been identified as an important aspect of the higher education experience (Cole et al, 2007). A study conducted by Hancock et al (2012) revealed that youth perceptions of their leadership skills are influenced by extracurricular activity involvement and support of their parents and other adults.…”
Section: Introductionmentioning
confidence: 99%